Analisis Kebutuhan Pengembangan LKPD IPA Berbasis Eksperimen Sains untuk Meningkatkan Minat Belajar Siswa di Sekolah Dasar - Liana Prabandari*; Djalal Fuadi; Sumardi Sumardi; Minsih Minsih; Yeny Prastiwi (Universitas Syiah Kuala, 2022)
Teaching materials are needed by teachers and students to facilitate the learning process, appropriate LKPD will greatly assist learners in understanding lessons that require practice or hands-on experience. IPA learning is one of the materials that require experimental activities. Science experiments are learning methods in natural science that provide opportunities for students to experience an experiment themselves so as to find answers to various problems. The description of the analysis of participants' worksheet development needs (LKPD) based on science experiments on the learning of elementary school science (SD) class V became the focus of this research. This research uses qualitative methods with this type of case study research. The subject of study consisted of three V-class teachers from SD Negeri in remote areas of Eromoko Subdistrict, Wonogiri Regency. The subject of the study was determined by purposive sampling which was based on the teacher with the highest number of learners in the class. The technique of collecting data is taken with interviews, questionnaires, and documentation. The technique of analyzing data used in this study are milles and hubberman analysis techniques. Test the validity of data used triangulation techniques. The results of this study show that IPA learning activities still use conventional methods with lectures and assignments, there is no LKPD that facilitates students to carry out practicum activities with science experiment methods, therefore based on the analysis of needs in the field, it is necessary to hold the development of science experiment-based LKPD IPA for elementary school V grade students